INDIVIDUAL PROBLEM SOLVING SHARED READING TO DEVELOP STUDENTSâ READING COMPREHENSION - Angelianawati, Luh (Jurnal Dinamika Pendidikan, 2016)
ABSTRACTTeaching English as a Foreign Language is challenged to find strategies which develop student-centered learning and be able to cultivate studentsâ language competence and performance effectively. Shared reading is affirmed as one of effective strategies to develop student-centered learning. The strategy is recognized as a creative and exciting model for active learning by doing a group or student-sharing. It makes students learn how making connections, predicting, asking questions, understanding new vocabulary, and making inferences. The main purpose of applying this strategy is to make the students have knowledge of vocabulary and concepts of print and literature reading, as well as use the language through collaborative reading experience. In implementing this strategy, the level of education in which the strategy is implemented should be considered. The way how this strategy may be utilized in the classroom is presented in this article.Keywords: shared reading, teaching strategy, student centered learningABSTRAKPengajaran Bahasa Inggris sebagai Bahasa Asing ditantang untuk menemukan strategi yang mampu mengembangkan pembelajaran yang berpusat pada siswa dan mampu menumbuhkan kemampuan berbahasa dan kinerja siswa secara efektif. Membaca bersama diakui sebagai salah satu strategi yang efektif untuk mengembangkan pembelajaran yang berpusat pada siswa. Strategi ini diakui sebagai model pembelajaran aktif yang kreatif dan menarik dengan cara belajar bersama kelompok. Hal tersebut membuat siswa belajar bagaimana menghubungkan informasi, memprediksi, mengajukan pertanyaan, memahami kosa kata baru, dan membuat kesimpulan. Tujuan utama dari penerapan strategi ini adalah untuk membuat siswa memiliki pengetahuan kosa kata dan konsep tentang bacaannya, serta menggunakan bahasa melalui pengalaman membaca kolaboratif. Dalam menerapkan strategi ini, tingkat pendidikan di mana strategi ini dilaksanakan harus dipertimbangkan. Cara bagaimana strategi ini dapat dilakukan di dalam kelas disajikan dalam artikel ini.Kata kunci: membaca bersama, strategi pengajaran, pembelajaran berpusat pada siswa